Izpeljava samostalnikov iz glagolov - Logar, Nataša (Slovenščina 2.0, 2018)
This paper discusses the understanding of word-formation productivity, as was founded by Harald Baayen at the end of the 1980s and in the early 1990s. Baayen's method of calculating productivity P is based on corpus linguistics methodology, therefore by using data from the Kres corpus, a corpus of written Slovene, we tested the method on the following ten Slovene suffixes, which all form noun derivatives from verbs (gender: masculine, meaning: human agent): -vec, -telj, -ež, -uh, -avh, -ar, -lec, -ač, -aj, and -ant. Among other findings, one was indicative: the number of derivatives with a certain suffix, and the productivity P of that same suffix could be (quite) diverse. For example: the suffix that had the largest number of derivatives was -lec, while the suffix -ež had the highest P score. On the basis of the data from the corpus, we then presented a list of the ten aforementioned suffixes along with example derivatives, i.e. the list, that could be part of a new grammar of Slovene. We also briefly commented on it and then, in the final discussion, pointed out some advantages and disadvantages of the approach presented.
Keywords: Baayen, Harald; besedotvorje; besedotvorna produktivnost; derivative; grammar; korpus Kres; Kres corpus; priponsko obrazilo; Slovene; slovenščina; slovnica; suffix; tvorjenka; word-formation; word-formation productivity